Combined TNF-α -308 (rs1800629) genotype and TyG index for identifying metabolic syndrome in a Vietnamese adult cohort - Tuan, Nguyen Huu Ngoc; Ha, Nguyen Minh (Tạp chí Nghiên cứu Y học, 2026)
The triglyceride-glucose (TyG) index is a robust surrogate for insulin resistance. This study evaluated the diagnostic and discriminative utility of combining the TyG index with the TNF-α -308G>A (rs1800629) genotype for early identification of Metabolic Syndrome (MetS) in a Vietnamese cohort, accounting for Metabolic Dysfunction-Associated Steatotic Liver Disease (MAFLD). This cross-sectional analysis included 311 medical and administrative staff. MetS was defined by harmonized criteria. The TyG index and TNF-α -308 genotypes were analyzed using multivariable logistic regression and Area Under the Receiver Operating Characteristic (AUC-ROC) curves, with stratification by MAFLD status. MetS prevalence was 17.4%. The TyG index was a highly significant independent discriminator of MetS (Adjusted OR = 59.73, p < 0.001). The TNF-α -308 A-allele carrier status did not significantly associate with MetS (Adjusted OR = 0.26, p = 0.120). The combined model yielded an AUC of 0.955 versus 0.952 for the reference model (ΔAUC = +0.003). While incremental AUC was slightly higher in the MAFLD subgroup (ΔAUC = +0.014), the synergistic effect was not statistically significant. The TyG index demonstrates excellent diagnostic utility for MetS. However, incorporating the TNF-α -308 genotype does not provide clinically meaningful incremental discriminative value in this population.